1997
DOI: 10.1161/01.cir.95.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Elective Stenting of the Extracranial Carotid Arteries

Abstract: In a high-risk group of patients, percutaneous carotid angioplasty and stenting are feasible and can be performed with low restenosis and repeat intervention rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
291
5
17

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 633 publications
(325 citation statements)
references
References 13 publications
12
291
5
17
Order By: Relevance
“…Mais recentemente, os trabalhos mostram taxas que variam de 1 a 7,5%, nos pacientes sem comorbidades, podendo chegar até a 18% nos pacientes com coronariopatia prévia 4,5,[16][17][18] .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Mais recentemente, os trabalhos mostram taxas que variam de 1 a 7,5%, nos pacientes sem comorbidades, podendo chegar até a 18% nos pacientes com coronariopatia prévia 4,5,[16][17][18] .…”
Section: Discussionunclassified
“…Porém deve-se lembrar que os pacientes com comorbidades, tais como diabetes, infarto de miocárdio prévio, hipertensão arterial sistêmica (HAS), entre várias outras, foram excluídos destes estudos, apesar da alta incidência de associação entre estas doenças e a doença ateromatosa da caró-tida, tornando limitada a reprodutibilidade desses resultados [5][6][7]20,21 . É importante ressaltar que, até pouco tempo atrás, os pacientes encaminhados a angioplastia eram aqueles com algum tipo de contraindicação a cirurgia, com alto risco de complicações 10,14,17,19,20 , ou previamente submetidos à endarterectomia carotídea.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Significant information about safety and feasibility of stenting was derived from large case series with periprocedural stroke and mortality and patency not too dissimilar from CEA trials. 25 An international survey by Wholley et al, 26,27 from major centers perform-ing CAS, reported 12 392 procedures performed in 11243 patients and suggested an acceptable periprocedural stroke and mortality of 4.75% that falls somewhere between NASCET and ACAS rates. The validity of these results is hampered by the uncontrolled nature of the data and potential verification and reporting bias of complications.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%